2008
DOI: 10.1007/s00436-008-1153-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization, distribution and prevalence of avian pox and avian malaria in the Berthelot’s pipit (Anthus berthelotii) in Macaronesia

Abstract: Exotic pathogens have been implicated in the decline and extinction of various native-island-bird species. Despite the fact that there is increasing concern about the introduction of diseases in island ecosystems, little is known about parasites in the islands of Macaronesia. We focus on Berthelot's pipit (Anthus berthelotii), an endemic and widespread Macaronesian bird species, using a combination of field studies and molecular techniques to determine: (1) the range and prevalence of avian pox and malaria in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 44 publications
1
60
0
2
Order By: Relevance
“…For avian malaria, no Haemoproteus was detected, but two Plasmodium strains were identified. These same strains were detected in Berthelot's pipits by Illera et al (2008). In the present study, the most common Plasmodium strain, TF413, was found in all but two of the individuals infected with Plasmodium.…”
Section: Molecular Characterization and Prevalence Levelssupporting
confidence: 71%
See 2 more Smart Citations
“…For avian malaria, no Haemoproteus was detected, but two Plasmodium strains were identified. These same strains were detected in Berthelot's pipits by Illera et al (2008). In the present study, the most common Plasmodium strain, TF413, was found in all but two of the individuals infected with Plasmodium.…”
Section: Molecular Characterization and Prevalence Levelssupporting
confidence: 71%
“…No evidence for trypanosome infection was found in any of our samples, despite the successful amplification of trypanosome DNA from positive controls. For avian pox, successful amplification was achieved in seven samples from 2006 (six from Porto Santo and one from Lanzarote), all of which gave identical sequences, apparently unique to Berthelot's pipit (Illera et al 2008). We were unable to achieve amplifications from any 2009 samples (discussed later).…”
Section: Molecular Characterization and Prevalence Levelsmentioning
confidence: 75%
See 1 more Smart Citation
“…The lifestyle of wild birds allows avian poxviruses to reach new hosts through bird migration, species introductions, and habitat change. Avian pox has been identified as an important risk factor in the conservation of small and endangered populations, particularly in island bird species (4). The impact of the introduction of avian pox has been disastrous for the avifauna of various archipelagos (11).…”
Section: Fowlpox Virus Canarypox Virus Juncopox Virus Mynahpox Virmentioning
confidence: 99%
“…In passerine birds (Passeriformes) from the family Paridae, the avipoxvirus infection has been described in tufted titmouse (Baeolophus bicolor) in the USA (Goodpasture and Anderson 1962), African blue tit (Cyanistes teneriffae) in the Canary Islands (Illera et al 2008), and great tit (Parus major) in Europe (Holt and Krogsrud 1973;Literak et al 2004;Gruber et al 2007;Palade et al 2008). The fact that great tits are among species susceptible to avipoxvirus infection was proven by experimental infections already in 1901 (Polowinkin 1901).…”
Section: Introductionmentioning
confidence: 98%